2022
DOI: 10.1007/s11027-021-09991-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate change adaptation (CCA) research in Nepal: implications for the advancement of adaptation planning

Abstract: Climate change has become one of the most compelling fields of empirical research over the last couple of decades, partly due to its socio-economic impacts. Using a meta-analysis of 235 peer-reviewed articles published between January 2010 and July 2020, this paper appraises climate change adaptation (CCA) research in Nepal and draws lessons for future adaptation planning. The number of research is observed to have increased significantly in recent years (2015-2020) although there is no consistent pattern over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A study of Makwanpur, which is a local area of agricultural production, found that alterations to the traditional cropping patterns and calendar, changing crop varieties and increased fertilizer and pesticide applications were required to maintain crop yields (Shrestha and Nepal, 2016). This report is supported by other recent studies of climate change impacts on agricultural farmland in Nepal (Bista et al ., 2021; Bocchiola et al ., 2019; Chaudhary et al ., 2021; Karki et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of Makwanpur, which is a local area of agricultural production, found that alterations to the traditional cropping patterns and calendar, changing crop varieties and increased fertilizer and pesticide applications were required to maintain crop yields (Shrestha and Nepal, 2016). This report is supported by other recent studies of climate change impacts on agricultural farmland in Nepal (Bista et al ., 2021; Bocchiola et al ., 2019; Chaudhary et al ., 2021; Karki et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The adaptation strategies that NAPA promotes are economically viable, environmentally friendly, locally available and socially adaptable. This finding is consistent with previous studies that reported on the need for a LAPA based on local planning, the adaptive capacity of vulnerable households and local- and national-level mainstreaming strategies (Acharya et al ., 2015; Gentle et al ., 2014; Karki et al ., 2022; Lamichhane et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of medicinal plants is supported by countries’ rich biodiversity [ 12 ], over 125 ethnic groups [ 13 ], and five disparate physiographic regions [ 14 , 15 ]. In the face of climate change [ 16 ], land use change [ 17 ], outmigration, and sociocultural and economic transformations [ 18 ], the tradition of medicinal plant collection and use in remote and rural areas has undergone significant changes in the recent decades [ 19 , 20 ]. Following predicted climate change, the population of medicinal plants is likely threatened, and the suitable habitat range for medicinal plants is likely to be shrink, resulting in significant alteration of traditional collection sites and practices [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation plans represent a way in which local individuals, households, and communities can change their mix of productive activities and modify their community rules and institutions in response to vulnerability to sustain their livelihoods [1]. Localized experience and observation-based knowledge is crucial with respect to climate change adaptation science [2]. The adaptation process is necessary to understand vulnerable systems, drivers of vulnerability, differential vulnerability, and local adaptive capacities to address risks and resilience to the impacts of climate change [3,4].…”
Section: Introductionmentioning
confidence: 99%